1996
DOI: 10.1080/15216549600201222
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemical studies on human, bovine and pig brain regulatory subunits of cAMP‐dependent protein kinase type II

Abstract: Regulatory subunits type II (RII) purified from human, pig and bovine brains were compared using 11 monoclonal antibodies (MoAb) against bovine brain RII. Bovine RII has at least 5 antigenic sites located in the N‐terminal 1‐110 residues. Immunochemical difference detected between human and animal RII was more pronounced than between pig and bovine RII. Certain MoAb influenced R‐cAMP binding and holoenzyme formation. RII of the three species responded to MoAb attachment in a similar fashion. The results sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…It is known that binding of cAMP of the R subunit of inactive cAMP‐dependent protein kinase leads to enzyme activation. MoAb used in the present study were previously shown to inhibit cAMP binding to the neural RII in vitro [1, 2]. So abolition of cAMP‐induced protein kinase activation in the presence of MoAb can indicate the formation of an immune complex.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…It is known that binding of cAMP of the R subunit of inactive cAMP‐dependent protein kinase leads to enzyme activation. MoAb used in the present study were previously shown to inhibit cAMP binding to the neural RII in vitro [1, 2]. So abolition of cAMP‐induced protein kinase activation in the presence of MoAb can indicate the formation of an immune complex.…”
Section: Resultsmentioning
confidence: 64%
“…Formation of the immune complex manifested itself in inhibition of cAMP binding. So, the inserted MoAb 6 cross‐reacted with RII of PC12 cells and produced remarkably the same effect in vivo as in vitro on isolated bovine, pig and human brain RII [2].…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Also, we have developed a procedure for more detailed elucidation of the role of cAMP‐dependent protein kinases (of intracellular cAMP‐dependent protein kinase, in particular) in the regulation of cell metabolism—a procedure that makes it possible to modulate these enzyme activities in live cells. To this end, we obtained monoclonal antibodies to the regulatory subunit RIIβ isolated from bovine brain 31,32. Depending on their effects on RIIβ, these antibodies can be classified into three groups: inhibiting, activating, and so‐called neutral antibodies—those that do not interfere in the reaction of RIIβ with cAMP or the catalytic subunit of protein kinase (Table 5).…”
Section: Basic Features Of Protein Kinases From Pig Brain and Physarumentioning
confidence: 99%
“…To this end, we obtained monoclonal antibodies to the regulatory subunit RIIβ isolated from bovine brain. 31,32 Depending on their effects on RIIβ, these antibodies can be classified into three groups: inhibiting, activating, and so-called neutral antibodies-those that do not interfere in the reaction of RIIβ with cAMP or the catalytic subunit of protein kinase (TABLE 5). Attachement of activating antibodies to RIIβ enhanced the ability of the latter to bind cAMP.…”
mentioning
confidence: 99%